The meaning and change in the function of communal space in Lamin house - Radja, Abdul Mufti; Harisah, Afifah; Sir, Mohammad Mochsen; Baharuddin, Faizal (ARTEKS : Jurnal Teknik Arsitektur, 2024)
In the modern era, many traditional houses have changed to functional spaces, as stated in several journals, including the Lamin house in East Kalimantan. The changes in spaces of traditional houses are caused by factors such as modernization, the economy, society, and others. Lamin houses, which have communal spaces with activities, have also shown indications of changes in functions. Therefore, the research purpose is to identify the changes in functions and their contributing factors, as well as to explore the meanings behind these functions. This research utilized a qualitative descriptive method with a phenomenological approach. Data collection techniques involved in-depth interviews and observations. The research findings indicate a shift in the functions of Lamin houses, which has an impact on the meaning of space and the addition of functions, accompanied by the meaning of behavior that maintains cultural aspects and encourages the economic sector. The factor causing the change is that the communal space has increased its tourism function. It is hoped that the results of this research will become the basis for maintaining the sustainability of the Lamin house as local architectural wisdom.